Analysis on the disclosure of environmental provisions and contingent liabilities in the market value of high-polluting companies listed on the stock exchange - Souza, Josiane Aparecida Cardoso de; Machado, Beatriz Cristina Ferreira; Cunha, Rodolfo de Souza; Oliveira, Mário César Fialho de; Oliveira, Patricia Werneck Silva de (Brazilian Journal of Production Engineering, 2021)
This work aimed to analyze the impacts of the disclosure of environmental provisions and contingent liabilities on the market value of companies with high polluting potential listed on B3. A total of 34 companies listed on the Stock Exchange were considered, which, according to Law 10,165/2000, which refers to the National Environmental Policy, belong to the high polluting impact group. For this study, a content analysis was performed to identify the disclosure of environmental provisions and contingent liabilities in the year 2020. Afterwards, a descriptive analysis was performed to investigate the distribution and behavior of the variables, as well as the execution of a regression by the OLS to verify the research hypothesis. To assess the link between the variables, Pearson's correlation was used. Between the independent variable (DIVULG) and the Market Value, the result was not statistically significant, therefore the initial hypothesis that the disclosure of environmental provisions and contingent liabilities has a positive impact on the market value of companies with high polluting potential listed in B3, was rejected, showing that such disclosure does not reflect the market value of these companies. The Company Size variable denoted statistical significance, showing that the larger the company size reflects its Market Value more, and the Return on assets variable had negative significance with the Market Value. Indebtedness did not show statistical significance, thus, it is not relevant to justify the market value of the companies evaluated.
Keywords: Environmental Provisions and Contingent Liabilities; Potentially Polluting Companies; Market value; Environmental Disclosure